2015
DOI: 10.1111/evj.12439
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction‐based national surveillance programme to determine the distribution and prevalence of Taylorella equigenitalis in South African horses

Abstract: T. equigenitalis was present in a subpopulation focus within the South African horse population prior to the outbreak identification in April 2011. Horizontal fomite-associated spread was the most probable route of transmission between stallions. The targeted surveillance of stallions and exposed mares using a qPCR-based screening programme expedited investigation of the distribution and prevalence of T. equigenitalis infection in South African horses. The application of qPCR provided a sensitive and practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…In addition, this study used swabs transported in Amies transport medium, which may not be the optimal medium for PCR purposes . A change to dry swabs for PCR might further increase the sensitivity of the PCR ; nevertheless, the results obtained in this study support the sensitivity of pooling with the current swab type.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, this study used swabs transported in Amies transport medium, which may not be the optimal medium for PCR purposes . A change to dry swabs for PCR might further increase the sensitivity of the PCR ; nevertheless, the results obtained in this study support the sensitivity of pooling with the current swab type.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, polymerase chain reaction assays (PCR) have been developed which rapidly detect the organism directly from genital swabs; the analytical sensitivity of PCR has been shown to be equivalent to selective culture methods . In addition, studies in Japan , Switzerland and South Africa have used direct PCR on genital swabs to screen large numbers of horses for disease eradication.…”
Section: Introductionmentioning
confidence: 99%
“…however, due to their similar growth requirements, morphology and biochemical characteristics, it is important to differentiate T. asinigenitalis from T. equigenitalis. This can be achieved by using molecular methods, with species specific primers, preferably qPCR, which also increases test sensitivity and significantly shortens turnaround time (WakeLeY et al, 2006;MaY et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiologic findings during the initial outbreak investigation suggested a point introduction of T. equigenitalis into South Africa prior to outbreak identification in May 2011. 13 It also indicated that current stringent pre-and postentry CEM importation screening procedures of all equids entering the country, implemented in the early 1980s, have to Table 1. Taylorella equigenitalis isolates (n = 36) obtained from crude extract of samples (genital swabs, n = 34; frozen semen samples, n = 2) collected in South Africa in 1996-2017.…”
mentioning
confidence: 99%
“…This inventory originated from samples obtained during both a nationwide stallion screening program, legislated subsequent to outbreak recognition, and an epidemiologic traceback. 13 Heightened awareness of the CEM-associated risk in South Africa prompted additional voluntary submissions of cryopreserved semen straws derived from ejaculates collected and processed from stallions prior to outbreak identification in 2011. In 2015, this submission of cryopreserved semen identified an additional T. equigenitalis –positive case linked to a stallion that had semen collected and cryopreserved in 2008.…”
mentioning
confidence: 99%